Animali maravigliosi Orientalismo e animali esotici a Firenze in epoca tardogotica e rinascimentale: conoscenza, immaginario, simbologia - Lurati, Patrica (Itinerari, 2021)
The research analyses the knowledge, the presence and the depiction of exotic animals in Florence from the late 14th century to 1492, year of Lorenzo de' Medici's death and of the discovery of the Americas. This well-documented interdisciplinary research sheds new light on a topic mainly neglected.